PENGEMBANGAN MEDIA BACA TULIS AL-QUR’AN BERBASIS YOUTUBE PADA SISWA INKLUSI - Febriana, Atiyah Azza Amaliyah; Yusuf Sya’bani, Mohammad Ahyan (Fakultas Agama Islam Universitas Muhammadiyah Luwuk, 2024)
Currently, advances in information and communication technology have developed, one of which is YouTube. From the YouTube application we can learn to understand the reading of the Al-Qur'an. The Qur'an is the final holy book revealed by Allah SWT to His prophets and apostles. This book of the Qur'an was revealed to the Prophet Muhammad SAW. Apart from being in the form of a book, Allah SWT also sent down His revelations in the form of pages (suhuf). One of the functions of the Koran is to perfect the previous holy book and also straighten out things that have come out of the teachings of that book. For this reason, the aim of this research is to see how YouTube-based Al-Quran reading and writing media is developed for inclusive students at Muhammadiyah 4 Giri Middle School. This research uses qualitative descriptive research, with data collection through interviews, observation and documentation where the research subjects are inclusive children and teachers. The results of this research show that the development of YouTube-based Al-Qur'an reading and writing media at Muhammadiyah 4 Giri Middle School is effective because students can pay attention when the teacher explains and the students' responses are also very active.